The Impact of COVID-19 on Risky Behaviors and Health Changes in African-American Smokers Who Are Eligible for LDCT Screening - Tseng, Tung-Sung; Li, Mirandy; Kao, Yu-Hsiang; Chen, Lei-Shih; Lin, Hui-Yi (Frontiers in Public Health, 2021)
The COVID-19 pandemic has disrupted much of day-to-day life in the US and around the world. Smokers have a higher risk of adverse outcomes due to COVID-19. This study investigated the impact of COVID-19 on risky behaviors and health changes in lower income African-American smokers eligible for Low dose computed tomography (LDCT) screening, who may be more adversely impacted by the COVID-19 pandemic. A total of 22 African-American daily smokers who were eligible for LDCT screening participated in this study. The mean age of participants was 61.2 years old (SD = 4.7), 77.3% of the smokers were female, all participants had an income below 20,000, and 63.6% were on Medicaid. Descriptive statistics were used to provide summary information on demographics, COVID-19, and health status. Results showed that participants increased cigarette smoking, spent more time on screens, increased sugary drink consumption, consumed more vegetables and fruits, and engaged in more gardening activities during the COVID-19 pandemic. However, participants also decreased physical activity time and slept less during the pandemic. In general, more than one-third of participants gained more body weight and reported increased stress and anxiety. Our results suggest that African-American smokers who qualify for LDCT screening should be encouraged to consider strategies not only for smoking cessation, but also risky behavior control and management.